Air nicotine monitoring for second hand smoke exposure in public places in India - Jagdish Kaur; Vinayak M Prasad (Wolters Kluwer Medknow Publications, 2011)
Background: Air nicotine monitoring is an established method of measuring exposure to second hand smoke (SHS). Not much research has been done in India to measure air nicotine for the purpose of studying exposure to SHS. It is a risk factor and many diseases are known to occur among non smokers if they are exposed to second hand smoke. Objective: To conduct monitoring of air nicotine for second hand smoke exposure in public places across major cities in India. Materials and Methods: A cross sectional survey was conducted across four cities across the country, using passive air monitoring. The buildings included hospitals, secondary schools, Governmental offices, bars and restaurants. The buildings were selected through convenience sampling method keeping in view specific sentinel locations of interest. Result: The presence of air nicotine was recorded in most of the buildings under the study, which included government buildings, hospitals, schools, restaurants and entertainment venues (bars) in all four cities under the study. The highest median levels of air nicotine were found in entertainment venues and restaurants in cities. Conclusion: The presence of air nicotine in indoor public places indicates weak implementation of existing smoke free law in India. The findings of this study provide a baseline characterization of exposure to SHS in public places in India, which could be used to promote clean indoor air policies and programs and monitor and evaluate the progress and future smoke-free initiatives in India.